The Impact of Live Streaming and Online Customer Reviews on Repurchase Intention in Tiktok Shop with Customer Satisfaction as an Moderation - Ridwan, Ridwan Maulana; Setiawan, Rahyuniati; Oktavia Herlianti, Anggun (Institut Agama Islam Negeri Kendari, 2025)
This study investigates the effect of live streaming and online customer reviews on repurchase intention with customer satisfaction as a moderation on TikTok Shop. Because live streaming and online customer reviews play an important role in the sustainability of a TikTok Shop, with that added to the customer satisfaction aspect can affect a repurchase intention. The quantitative method was used with a sample of 108 online shop customers selected through simple random sampling. Data was collected through a questionnaire and analyzed using Structural Equation Modeling with SmartPLS 3.0 version. These findings confirm that Live Streaming and Online Customer Reviews have a significant direct effect on Repurchase Intent, but Live Streaming has no significant effect on Customer Satisfaction. In addition, Customer Satisfaction has a strong positive effect on Repurchase Intention and significantly moderates the relationship between Live Streaming and Repurchase Intention, but not on the Online Customer Reviews aspect. These findings highlight the integration of live streaming and reviews as a path to increase the aspect of repurchase intention on TikTok Shop. Observing the results of the indirect effect of the result, researchers consider that the role of customer satisfaction is not vital, and may change customer behavior.